The Barriers of Medical Tourism Hospital Development in Medan - Marizka Jasmine; Ida Yustina; Zulfendri Zulfendri (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Medan residents are known to prefer traveling to Malaysia and Singapore for medical treatment. This phenomenon leads to huge losses in regional and national revenues. In response to this phenomenon, by 2021, the Medan City government has implemented the Medan medical tourism program, with the participation of twelve hospitals located in Medan to be prepared as medical tourism destinations, but until 2024, none of the Medan or North Sumatra residents have made use of this program. The objective of this study is to explore the barriers on the development of medical tourism hospitals in Medan. Using a qualitative method with a phenomenological approach, this research was conducted through in-depth interviews, observation, and documentation from eight hospitals within the Medan medical tourism program. This study identified several key barriers: healthcare system issues, poor medical infrastructure, limited continuity of care, inadequate hospital promotion of Medan medical tourism program, lack of international accreditation, lack of ISO certification, unavailability of medical equipment, failure to meet national indicators of hospital quality, and unfriendliness of doctors and staff. The findings indicate that hospitals in Medan need significant improvements in various aspects to become competitive in the medical tourism market. Furthermore, to overcome these barriers, coordinated and sustained efforts from the hospitals, Medan City government, Medan medical tourism board and Medan tourism department are needed to transform hospitals into medical tourism destinations despite the gradual and lengthy process. Keywords: Barriers, Development, Hospitals, Medical Tourism